An investigation into the hedging practices of U.S. and non-U.S. airlines - Michael, Senior (2016)
This study aims to draw comparisons between data gathered from a sample of U.S. airlines and data obtained from a sample of non-U.S. airlines to investigate the hedging practices of both. It attempts to examine whether or not more lenient bankruptcy codes as seen with Chapter 11 in the United States, has an effect on an airline’s decision to hedge. The full sample consists of 50 of the world’s largest airlines based on market capitalisation which is made up of 11 airlines from the United States and 39 from the rest of the world. Data was collected over a period of 14 years from 2002 – 2015. The study used a number of tests including univariate and multivariate tests. These showed that liquidity was a key determinant on whether or not a firm hedged, which therefore offers support to the theory that a lack of internal funds creates hedging incentives. Another key determinant was the size of the airline, which also offered support to the notion that larger firms are more likely to hedge to take advantage of their economies of scale. The interest coverage measure produced mixed results whereby it was an important determinant for non-U.S. airlines’ decision to hedge, however it was insignificant for U.S. airlines. One of the explanations for this may be the Chapter 11 bankruptcy provision that provides bankrupt U.S. firms with a huge competitive advantage over their international competitors, who are based in countries with credit-favouring bankruptcy codes. The inability of non-U.S. airlines to trigger a second chance bankruptcy provision, and avoid liquidation, is clearly an important factor on whether or not to hedge.